2022
DOI: 10.3390/batteries8070073
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Fuel-Cell and Battery Technologies in Unmanned Aerial Vehicles (UAVs): A Dynamic Study

Abstract: The harmful impacts of fossil-fuel-based engines on the environment have resulted in the development of other alternatives for different types of vehicles. Currently, batteries and fuel cells are being used in the automotive industry, while promising progress in the maritime and aerospace sectors is foreseen. As a case study in the aerospace sector, an unmanned aerial vehicle (UAV) was considered. The goal and the novelty of this study are in its analysis of the possibility of providing 960 W of power for a UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Unlike the study in [298], the work in [300] suggested a hybridization between gasoline and electric motors: two gasoline motors supplied the majority of the power needed for the lift force, with four electric motors utilized to stabilize the drone. Since the propellers consume the majority of the power within a UAV, the suggested gasoline-electric hybrid method prolongs a UAV's flight time.…”
Section: Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the study in [298], the work in [300] suggested a hybridization between gasoline and electric motors: two gasoline motors supplied the majority of the power needed for the lift force, with four electric motors utilized to stabilize the drone. Since the propellers consume the majority of the power within a UAV, the suggested gasoline-electric hybrid method prolongs a UAV's flight time.…”
Section: Powermentioning
confidence: 99%
“…Beginning with the work in [298], a 14 kg UAV had a power of 960 W supplied from a hybrid system, which was composed of a proton-exchange membrane fuel cell (as the main supply) and a Li-I (as a backup). This power-source mixture took advantage of the fuel cells fast refueling and ability to supply power for long distance ranges, in addition to the Li-I high acceleration and fast response to load variations.…”
Section: Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The onboard power system is demanded to provide long-flight endurance in both vertical flight and level flight. However, what must be pointed out is that most all-electric VTOLs (eVTOLs) lack flight endurance, limited to the energy density of lithium battery packs [1][2][3][4] . Some existing compound-wing VTOLs are installed with both ICE and battery powered unit, but these ICE and batterypowered units are operated independently during the whole flight profile: the former is used in level flight, and the latter powers in vertical take-off and landing (including hovering) [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their improved stability and endurance in many missions, unmanned aerial vehicles (UAVs), often called drones, have garnered significant contributions in various civilian and military service disciplines [1]- [3]. UAV uses are developing significantly as a result of their cutting-edge utilization in the internet of things (IoT) and fifth-generation [4].…”
Section: Introductionmentioning
confidence: 99%